Transformation from natural (thermal contraction) to anthropogenic (resource exploitation) depressions in the Krotoszyn-Koźmin-Raszków area (Polish Lowland) - Stankowski, Wojciech (Wydawnictwo Naukowe UAM, 2012)
An exceptional concentration of almost identical depressions exist near the small towns of Krotoszyn, Koźmin and Raszków (southern Wielkopolska). Their origin is, however, different from that of the typical post glacial-relief: they are Man-made enlarged thermal-contraction structures that developed at the very end of the Middle Polish (Warthian) glaciation and during the North Polish (Weichselian) glaciation, most probably under periglacial conditions.
Keywords: geomorphology; periglacial relief; anthropogenic relief; thermal-contraction; structures; Polish Lowland